PERUBAHAN ANTROPONIMI DALAM MASYARAKAT JAWA - Dwi Atmawati; Wening Purnami; Arif Izzak (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2022)
This anthroponymic research is focused on studying the proper names of Javanese people living in the Special Region of Yogyakarta (DIY). DIY was designated as the research location because it is one of the places that have historical value in Javanese civilization. In addition, in DIY there is also a palace which is rich in Javanese cultural values. This study aims to determine the proper name contained in DIY, whether there are still retaining Javanese elements or Javanese elements have been lost and replaced with proper names originating from other regions. The theory used in this study is the theory of anthroponymy by Crystal (2008). The data was collected by using the method of documentation, sampling technique, and interviews. This documentation method is used to obtain proper name data from written sources, such as print, electronic, and internet media. The informants were selected based on the criteria of being married and having children; Javanese ethnic; come from low, middle, and high social status. Data analysis used the contextual method. Based on this research, it is known that cultural acculturation and technological advances affect the choice of the proper name for the Javanese people in Yogyakarta. There has been a shift in naming children, from traditional Javanese to 'modern' names and to people's names of Arabic origin.Penelitian antroponimi ini difokuskan pada nama diri orang Jawa yang tinggal di Daerah Istimewa Yogyakarta (DIY). DIY ditetapkan sebagai lokasi penelitian karena merupakan salah satu tempat yang me-miliki nilai sejarah dalam peradaban Jawa. Selain itu, di DIY juga terdapat keraton yang kaya nilai-nilai budaya Jawa. Penelitian ini bertujuan untuk menjelaskan nama diri yang terdapat di DIY, apakah masih ada yang mempertahankan unsur Jawa atau unsur Jawa telah hilang dan diganti dengan nama diri yang berasal dari daerah lain. Teori yang digunakan dalam penelitian ini adalah teori antroponimi oleh Crystal (2008). Pengumpulan data dilakukan dengan metode dokumentasi, teknik sampling, dan wawancara. Metode dokumentasi ini digunakan untuk memperoleh data nama diri dari sumber tulis, seperti media cetak, elektronik, dan internet. Informan dipilih berdasarkan kriteria sudah menikah dan memiliki anak; bersuku Jawa; berasal dari status sosial rendah, menengah, dan tinggi. Dalam nalisis data digunakan metode kontekstual. Berdasarkan penelitian ini diketahui bahwa akulturasi budaya dan kemajuan teknologi berpengaruh pada pemilihan nama diri pada masyarakat Jawa di DIY. Telah terjadi pergeseran dalam penamaan anak, dari nama tradisional Jawa ke modern dan ke nama orang yang berasal dari bahasa Arab.